PENDIDIKAN ISLAM SEBAGAI MODAL RESILIENSI MENTAL DI ERA DIGITAL - Dimas Maulana Rahman; Miftahurrahmat (Yayasan An-Nur Meunara Baro, 2025)
The digital era has brought new challenges to the mental health of the Muslim generation, particularly among adolescents and students. Increased exposure to social media, virtual peer pressure, and digital fatigue have triggered psychological symptoms such as anxiety, stress, and identity crises. This article aims to explore how Islamic education can serve as a primary foundation for developing mental resilience in the digital age through a conceptual and literature-based approach. This study employs a qualitative method with a library research design, utilizing secondary data from reputable national and international journals published between 2019 and 2025. The findings reveal that the integration of Islamic values such as sabr (patience), shukr (gratitude), tawakkul (trust in God), and iffah (self-restraint) significantly contributes to emotional regulation and the formation of meaningful life perspectives. Practices such as Qur’an memorization (tahfiz), structured dhikr (remembrance of God), and nature-based learning grounded in sunnatullah are shown to positively enhance students' mental and spiritual endurance. Compared to secular psychological approaches that tend to be individualistic, Islamic education frames resilience as a holistic development of the soul, mind, and social self. The study recommends developing an integrative curriculum that incorporates spirituality, digital literacy, and Islamic psychoeducational strategies in formal education systems. Thus, Islamic education is not only value-relevant but also offers transformative solutions to the mental health crisis emerging from digital transformation.